2008
DOI: 10.1073/pnas.0811411106
|View full text |Cite
|
Sign up to set email alerts
|

Trop2 identifies a subpopulation of murine and human prostate basal cells with stem cell characteristics

Abstract: The epithelium of the adult prostate contains 3 distinct cell types: basal, luminal, and neuroendocrine. Tissue-regenerative activity has been identified predominantly from the basal cells, isolated by expression of CD49f and stem cell antigen-1 (Sca-1). An important question for the field is whether all basal cells have stem cell characteristics. Prostate-specific microarray databases were interrogated to find candidate surface antigens that could subfractionate the basal cell population. Tumor-associated cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
336
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 309 publications
(365 citation statements)
references
References 49 publications
27
336
1
1
Order By: Relevance
“…Rodent prostate basal epithelial cells are capable of adapting a luminal cell phenotype during in vitro culture (52). Several independent groups (19)(20)(21)(22)(23)(24)(25) have shown in a prostate regeneration assay that both human and rodent basal cells possess the capacity for multilineage differentiation. In the current study, we further showed that acute prostatic inflammation induced by bacterial infection significantly promoted basal-toluminal differentiation in situ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodent prostate basal epithelial cells are capable of adapting a luminal cell phenotype during in vitro culture (52). Several independent groups (19)(20)(21)(22)(23)(24)(25) have shown in a prostate regeneration assay that both human and rodent basal cells possess the capacity for multilineage differentiation. In the current study, we further showed that acute prostatic inflammation induced by bacterial infection significantly promoted basal-toluminal differentiation in situ.…”
Section: Discussionmentioning
confidence: 99%
“…Using a lineage-tracing approach, we and several other groups showed that adult murine prostate basal and luminal cell lineages are largely self-sustained when residing in their native microenvironment, although in two of the studies basal cells were shown to generate luminal cells at an extremely rare frequency (14)(15)(16)(17)(18). In stark contrast, other studies have shown that basal cells are able to differentiate very efficiently into luminal cells and neuroendocrine cells in a dissociated prostate-cell regeneration assay (19)(20)(21)(22)(23)(24)(25). In the prostate-cell regeneration assay, prostate basal epithelial cells were removed from their native environment, dissociated into single cells, and stimulated with embryonic urogenital sinus mesenchymal (UGSM) cells that have strong reprogramming activity (26)(27)(28).…”
mentioning
confidence: 97%
“…Isolated and dissociated endometrial cells were plated in matrigel coated six-well plates and the number and type of colonies were scored after 8 d based on morphology and expression of epithelial vs. stromal markers. Trop2 is a cell surface marker expressed in uterine epithelium (10) (Fig. 2A).…”
Section: Dissociated Endometrial Glands Were Highly Enriched For Epitmentioning
confidence: 99%
“…The lineage relationship between basal and luminal cells has recently been under heavy debate. Although renal capsule or subcutaneous transplantation experiments support the traditional view that basal cells have the ability to regenerate the prostate gland by repopulating all prostate epithelial lineages [1][2][3][4] , evidence from the rescued explants of p63-null mice suggest that luminal cells can sustain a prostate structure independently of basal cells 5 . In addition, with transgenic reporter mice, a population of castration-resistant Nkx3.1-expressing luminal cells has been shown to be able to generate not only luminal cells but also other prostatic epithelial lineages 6 .…”
mentioning
confidence: 97%